The Terrible Allure of Nuclear Weapons - Loo, Bernard Fook Weng (2016)
If Myanmar intends to acquire nuclear weapons, as reports suggest, this reflects a widely-held and terrible attraction that nuclear weapons maintain over military planners. This fascination stems from a misunderstanding about what nuclear weapons can do for a country’s national security.